Teachers’ Challenges in Integrating Digital Media in the Implementation of Merdeka Curriculum - Nadhifa, Nisa Aprilia Afyun; Madjid, Hilda Izzati; Rofiq, Ainur (ICONELT, 2024)
This study aims to analyze the challenges encountered by English teachers in integrating digital media in the Merdeka Curriculum. The research participants are two English teachers at an islamic senior high school in Sidoarjo. The data collected from the interview are analyzed in relation to both the issue of technology integration in the teaching and learning process and the Indonesian new curriculum framework. The role of learning media is very important the quality of learning, breaking down complex concepts, and engaging students in a more interactive way. This study applies a qualitative method with a case study approach, focused on two English teachers who teach in different classes. Based on the result of this study, it is hoped that stakeholders will get useful recommendations to design more effective strategies in supporting media integration in the context of education in Indonesia.